Influence of terminal sire breed on carcass and meat quality traits of pigs - Kušec, Goran; Kralik, Gordana; Gutzmirtl, Hrvoje; Petričević, Antun; Grgurić, Dražen (Acta Agraria Kaposváriensis, 2002)
The carcasses of 53 pigs were included in this study. They were divided in two groups according to the breed of the terminal sire as follows: 28 progenies of Large White and 25 progenies of Pietrain sire. Dams were all Large WhitexSwedish Landrace crossbreeds. Sire line had no influence on cold carcass weight, length and fat thickness measured as in „two points ” (TP) method of lean percentage estimation, as well as on ham length and ham index (P > 0.05). On the other hand, carcasses of the pigs originated from Pietrain sires had significantly higher thickness of MLD measured as in both TP and instrumental (FOM) method of lean percentage estimation, while fat thickness measured at the place of FOM method was significantly lower (P < 0.01). These carcasses had also higher estimated lean percentage, ham circumference and ham weight (P < 0.01). Although progeny of Pietrain sires performed better regarding the carcass traits, their meat quality was inferior compared with the meat of the pigs originated from Large White sires. The value of pH45 of the pigs originated from Pietrain sires was significantly lower, at the border of PSE meat, and Minolta L* values indicated significantly paler color than in the case of Large White crosses. Crosses with Pietrain had, however, higher MLD surface and fat/muscle ratio (P < 0.01) than Large White crosses. Other meat quality traits, such as pH24, water holding capacity, consistensy and fat surface, were unaffected by the breed of terminal sire.
Keywords: pig; breed; carcass; meat quality